Technical Reference Framework for the Interoperability of Electronic Medical Record: Conceptual Model - Morales-Rocha, V. M.; Olmos-Sánchez, K. M.; Barbosa-Ramírez, F.; Hernández-Hernández, J. I. (Revista Mexicana de Ingenieria Biomedica, 2020)
This paper presents the conceptual modeling of a technical framework of sharing and interaction of an electronic medical record among different healthcare institutions, both public or private, as a first step to establish a technical reference framework for the interoperability of electronic medical record systems in Mexico. The conceptual modeling was carried out using the KMOS-RE systematic process. Through this process, the following components have been obtained: the knowledge domain extended lexicon, the conceptual models, one for the application domain and another for the solution domain, as well as the state models. Since the design and implementation of the electronic medical record systems of different healthcare institutions are generated independently, having a technical reference framework represents a great challenge but also a great opportunity, since it will offer important advantages, such as having the clinical information in a timely manner in any healthcare institution, the possibility of the patient accessing their own information and the ease of conducting clinical research from the shared data. Having a precise conceptual model will facilitate the next steps to achieve the proposed technical reference framework.